THE RELATIONSHIP BETWEEN THE PHYSICAL QUALITY OF DUG WELLS AND THE INCIDENCE OF DIARRHEA IN MEUNASAH BALEE VILLAGE, LHOKNGA DISTRICT, ACEH BESAR REGENCY IN 2019 - Luvita, Aprillia Indri; Mawardi, Mawardi; Ariscasari, Putri (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Diarrhea is a significant public health problem in many countries, including Indonesia. Meunasah Balee Village in Lhoknga District has been identified as the area with the highest number of diarrhea cases at the local Health Center in 2017. This study aims to identify the relationship between the physical condition of dug wells and the incidence of diarrhea in Meunasah Balee Village. Method: The study was conducted using a descriptive analytical method with a cross-sectional design. The study population included all households (81 RT) that had dug wells. Data collection was in January-February 2019. Data were analyzed using the Chi-square test with the help of the SPSS 20 program. Result: The results showed a significant relationship between several physical factors of dug wells, the relationship between the distance of the septic tank with a p-value of 0.004, the distance of the pollutant source of 0.002, and the physical condition of the dug well with the incidence of diarrhea of 0.018. Laboratory examination results showed that all samples that experienced diarrhea (100%) did not meet the microbiological quality requirements based on the MPN (Most Probable Number) measurement. Recommendation: Recommendations were submitted to the Health Office to provide intensive counseling on the importance of providing clean water, managing septic tanks, and controlling sources of pollution as preventive measures to reduce the incidence of diarrhea in the area.